THE ROLE OF CASH FLOW FORECASTING SKILLS IN THE DEVELOPMENT OF ENTREPRENEURSHIP: AN EMPIRICAL STUDY OF ENTREPRENEURS IN THE COSMETICS ECOSYSTEM - Dennis , Nwaede (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2023)
There are growing media reports suggesting that the cosmetics industry in Nigeria is experiencing rapid growth and provides a veritable opportunity for entrepreneurial development. On the other hand, cash flow forecasting has been implicated in the growth and decline of entrepreneurship. However, little is known about the cash flow forecasting knowledge of many small business enterprises in Nigeria. The present study examined the cash flow forecasting knowledge among cosmetics entrepreneurs in River state, Nigeria. One hundred and seventeen small business enterprises conveniently selected from River state participated in the study. A self-developed instrument was used as a measure. The study adopted a cross-sectional survey design. The result was based on data from 41 (35%) retail businesses, 33 (28.2%) ICT operators, 16 (13.7%) small manufacturing firms, and 27 (23.1) engineering workshops in River state. Data were evaluated using the statistical package for social sciences (SPSS, version 23). A simple percentage formula was used to analyze the data to determine cash flow knowledge among the respondents. The result indicated that 78 respondents representing 66.7% of the total participants, scored high on cash flow knowledge, meaning they understand cash flow forecasting. The finding suggests that 39, representing 33.3% of the respondents, were not knowledgeable about cash flow forecasting. The result has implications for research and business analysis.